A simple FSDT-based meshfree method for analysis of functionally graded plates. (June 2017) - Vu, Tan-Van; Nguyen, Ngoc-Hung; Khosravifard, Amir; Hematiyan, M.R.; Tanaka, Satoyuki; Bui, Tinh Quoc
Abstract: Modeling of mechanical behavior of plates has been accomplished in the past decades, with different numerical strategies including the finite element and meshfree methods, and with a range of plate theories including the first-order shear deformation theory (FSDT). In this paper, we propose an efficient numerical meshfree approach to analyze static bending and free vibration of functionally graded (FG) plates. The kinematics of plates is based on a novel simple FSDT, termed as S-FSDT, which is an effective four-variable refined plate theory. The S-FSDT requires C 1 -continuity that is satisfied with the basis functions based on moving Kriging interpolation. Some major features of the approach can be summarized: (a) it is less computationally expensive due to having fewer unknowns; (b) it is naturally free from shear-locking; (c) it captures the physics of shear-deformation effect present in the conventional FSDT; (d) the essential boundary conditions can straightforwardly be treated, the same as the FEM; and (e) it can deal with both thin and thick plates. All these features will be demonstrated through numerical examples, which are to confirm the accuracy and effectiveness of the proposed method. Additionally, a discussion on other possible choices of correlation functions used in the model is given.